The Costs of Meeting the 2030 Sustainable Development Goal Targets on Drinking Water, Sanitation, and Hygiene - Hutton, Guy (World Bank, Washington, DC, 2016)
A dedicated goal for water has recently been endorsed by the United Nations General Assembly as part of the sustainable development goal (SDG) framework. This study provides an assessment of the global costs of meeting the WASH-related targets of Goal #6. The targets assessed include achieving universal and equitable access to safe and affordable drinking water for all (target 6.1), achieving access to adequate and equitable sanitation and hygiene for all, and ending open defecation (target 6.2). The estimates include 140 countries, or 85% of the world's population, focusing on developing countries. Costs estimated cover those of capital investment, program delivery, operations, and major capital maintenance.